Combined small-cell lung cancer with adenocarcinoma: a rare case and literatures review - Xiao Wu; Ke Fang; Wenya Huang; Gang Chen; Dingkun Wang (Journal of Cancer Research and Clinical Oncology)
Abstract Combined small-cell lung carcinoma (C-SCLC) is an uncommon lung cancer variant characterized by the presence of multiple pathological types within a single case or tumor, typically associated with poor outcomes. The high rate of misdiagnosis and low rate of accurate diagnosis for C-SCLC stem from limitations in sample collection, which primarily involves bronchoscopy and aspiration biopsy instead of surgical resection or autopsy. Moreover, standard chemotherapy for patients with C-SCLC has not yet been established. Cases of combined small-cell lung cancer with adenocarcinoma are extremely rare. Herein, we report a case of the detailed whole-process treatment of combined small-cell lung cancer with adenocarcinoma and review the literature.